Neoliberal legality as dual process: embeddedness, courts and crime prevention in the United States - Campeau, Holly (The British journal of criminology, 2019)
This article advances research on ‘neoliberal legality’ to focus on the role of courts in response to neoliberal crime prevention approaches. Drawing on Karl Polanyi’s analysis of embeddedness in market capitalism, along with criminological research on the penal state, we analyse three case studies reflecting central crime prevention approaches of the neoliberal era in the United States. We find that neoliberal legality is more complex than simply legitimating or resisting neoliberal policies. We highlight how courts did both at once—they moderated the harshest edges of neoliberal policies through alternative symbolic frames, yet in so doing also legitimated the core of neoliberal crime prevention efforts. We argue that neoliberal legality operates through this dual process, in which the basic thrust of neoliberalism is legitimated by also having policies moderated, recast and embedded within other social and juridical expectations.